Hijab and the Hegemony of Piety: Politization of Women’s Identity in Indonesia - Nenohai, Jear N. D. K.; Hakim, Fany N. R. (Faculty of Social and Political Sciences - UIN Walisongo Semarang, 2024)
The imposition of mandatory hijab in Indonesia is a growing concern that highlights tensions between religious expression and women’s rights. Despite Indonesia’s pluralistic ideas, the enforcement of hijab, for example in schools or public institutions, continues to affect women and girls, reflecting a broader struggle over religious authority and national identity. This study employs a qualitative approach through case studies of several incidents where women were compelled to wear the hijab. Data collection involved document analysis and media review to understand the socio-political and historical dynamics shaping hijab enforcement. Findings show that hijab enforcement persists in various public institutions, including schools, where women are pressured to conform to dress codes based on certain Islamic interpretations. This reflects the hegemonic entanglement of religion and politics in regulating women’s bodies. We identify diverse discourses within the Muslim community regarding the necessity of hijab, revealing internal contestation over religious interpretation. Moreover, the politicization of hijab is deeply rooted in Indonesia’s historical trajectory, including noninclusive education. These findings call for a critical repositioning of the hijab discourse in Indonesia, grounded in democratic values, gender equity, and religious inclusivity. __________The original draft of this article has been presented at the 23rd Annual International Conference on Islamic Studies (AICIS), February 1-4, 2024, at Universitas Islam Negeri Walisongo Semarang, Indonesia.